ALLITERATION AND ASSONANCE IN M. VINGRANOVSKI’S POETRY - Ковтун, С. Є. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the issue of alliteration and assonance in Mykola Vigranovski’s poetry. Their connection with other euphonic phenomena, as well as with the figures of speech and stylistic figures is traced. Special euphonic skills of the author are emphasized.